Effectiveness of Neem Oil and Jatropha Oil in Controlling Spodoptera frugiperda (J.E Smith) on Maize in the Republic of Chad - Mbaidiro Taambaijim’d Josue; Onzo Alexis (European Scientific Journal, ESJ, 2022)
Upon the evidence of its invasion in Chad in 2018, Spodoptera frugiperda has become a serious threat to maize production, thereby prompting farmers to a massive use of chemical pesticides to reduce its damage. However, given the adverse negative effects of chemical pesticides on human health and the environment, alternatives to chemical control are highly sought. In that respect, the effectiveness of Neem oil and Jatropha oil, two bio pesticides widely acknowledged for their insecticidal properties, was evaluated in the field in comparison with the chemical insecticide, Emamectin benzoate, in a Fisher Blocks design with 4 treatments and 4 replicates. The mean larval density per 25 plants was significantly the lowest (P < 0.0001) on Emamectin benzoate-treated plants(1.13 ± 0.70), followed by Jatropha oil (6.13 ± 0.87) and Neem oil treatments (7.13 ± 0.80) while the highest density was recorded on the untreated plants (12.31 ± 0.87). Similarly, the infestation rates were significantly lower on plots that received the chemical insecticide or the bio pesticides compared to the control plots (P < 0.0001). Foliar and ear damage scores were also significantly lower on the treated than on the control plots (P < 0.0001); and the number of ears attacked was significantly higher on the untreated control than on the other treatments. Maize grain yields were significantly higher in the treated plots compared to the control plots (P < 0.001). Yield gains over the control were 132.57%, 90.91% and 72.73% respectively for Emamectin benzoate, Jatropha oil and Neem oil treatments. It appears, therefore, that the use of Jatropha oil or Neem oil could significantly contribute to an effective and sustainable management of S. frugiperda on maize in Chad, thereby calling for the need for further investigations in that area in the frame of integrated pest management of this pest.